English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

cos4x-c0s2x
___________ = -sinx
2sin3x

2006-11-25 06:31:59 · 4 answers · asked by Ryan J 2 in Science & Mathematics Mathematics

4 answers

Anami's answer was correct and very simple. You should give him credit for it.

Here it is:

ID: cos(A+B)-cos(A-B)= -2sinAsinB
so RHS: A=3x and B=x
=> -2sin3xsinx = cos4x -cos 2x
proved.

What he did is this (only working with the left side):

cos4x - cos2x
------------------
2sin3x

cos(3x + x) - cos(3x - x)
------------------------------
2sin3x

cos3x cosx - sin3x sinx - (cos3x cosx - sin3x sinx)
-----------------------------------------------------------------
2sin3x

-2sin3x sinx
---------------
2sin3x

-sinx

is that more clear?

2006-11-25 07:25:45 · answer #1 · answered by Jim Burnell 6 · 0 0

cos4x-cos2x
----------------- = -sinx
2sin3x

LHS =

cos4x-cos2x
----------------- =
2sin3x

(2cos²2x - 1) - cos2x
---------------------------- =
2sin(2x + x)

2cos²2x - cos2x - 1
------------------ ------------------ =
2(2sin2xcosx + cos2x sinx)

(2cos2x + 1)(cos2x - 1)
-------------------- ---------------------- =
2(2sinxcos²x + (1 - 2 sin²x) sinx)

(2(1 - 2sin²x) + 1)((1 - 2sin²x) - 1)
--------------------- ---------------------- =
2(2sinx(1 - sin²x) + sinx - 2sin³x)

(2(1 - 2sin²x) + 1)((1 - 2sin²x) - 1)
---------------------- --------------------- =
2(3sinx - 4sin³x)

(3 - 4sin²x)( - 2sin²x)
--------------------------- =
2sinx(3 - 4sinx)

-sinx

= RHS ......................................... QED!!!!!!

2006-11-25 15:19:21 · answer #2 · answered by Wal C 6 · 0 0

are you sure it's correct cause i'm not coming up with the proof

2006-11-25 14:55:12 · answer #3 · answered by ? 2 · 0 0

already given answer previously check my answer again

2006-11-25 14:49:30 · answer #4 · answered by anami 3 · 1 0

fedest.com, questions and answers